INOVASI MODEL PEMBELAJARAN “BLACK MARKET” UNTUK MENDONGKRAK PEMAHAMAN KONSEP OPTIK : - - TEGUH SOEHARTO (LPMP Provinsi DKI Jakarta, 2022)
Abstract: Optical concepts are important concepts for understanding science. This research seeks to improve understanding of optical concepts, through the black market. In the academic year 2021–2022, the study was carried out at SMP Negeri 8 Cikarang Utara, Jawa Barat. This study employed three rounds of classroom action research. In light of the results, optical concepts were generally understood at an average level of 53.03 in the Pre-cycle, 61.10 in First Cycle: 67.43; Second Cycle: 67.43; Third Cycle: 77.83. The number of students who understand optical concepts has increased from 30 students, in Pre-cycle: 26.67% (8 students); 1st cycle: 46.67% (14 students); The second cycle: 63.33% (19 students) and the third cycle: 83.33% (25 students). Indicators of understanding optical concepts include: interpreting, exemplinifying, classifying, summarizing, inferring, comparing and explaining. The study's finding is that using the black market model to explain optical principles can help people grasp them better. The study's conclusions recommend that science teachers adopt the black market model to improve their pupils' understanding of optical principles. Keywords: Optical Concepts, Learning Models, Black Market Models